The Thermo-Entropic Limits of Security in Capital’s Militaristic Death Drive: A Note on Robert Biel’s Entropy of Capitalism - King, Robert Drury (Journal of Ecohumanism, 2023)
This commentary to Robert Biel’s book, The Entropy of Capitalism, defines the tasks of international security on the terms of a systems theory that asks how the system reproduces itself. The matter, energy, and information that go into its successful reproduction are also ecological challenges to this very system because the processes that generate the order of the system are the same processes that generate an entropy for the system that it must confront. The system confronts its own waste and the manner in which it does so, on Biel’s account, establishes its pathways of future development, including the ways in which the system is constrained. The commentary reaches beyond Biel’s framework by deepening his understanding of the structural embeddedness of capitalist development, including its surveillance stage, but it ends by defending Biel against his critics. Critics of Biel’s preference for low-input strategies of future development run astray, I suggest, in their neglect of Biel’s core insights into how an analysis of entropy is so essential to an understanding how the capitalist system works.